2016
DOI: 10.1177/1206331216646059
|View full text |Cite
|
Sign up to set email alerts
|

Urban or Family-Friendly? The Presentation of Czech Shopping Centers as Family-Friendly Spaces

Abstract: This article presents a study of the self-presentation of shopping centers in the Czech Republic as “family-friendly” spaces. The notion of family-friendliness is analyzed both as a structural category, referring to the structure of the stereotypical normal family and to its respective members, and as a cultural representation, referring to “family values,” which Czech malls invoke in their self-presentation. It is argued that the presentation of a “space for the whole family” covers only the persistent stereo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…1841(Atkinson, -1842 The notion of a "street without its dangers" is a crucial reference when considered in the context of the rise of privately owned commercial spaces, such as shopping malls and privately owned developments, squares, and plazas (Pratt, 2017). Researchers have shown that the idea of an urban or quasi-urban street without the dangers and unpredictabilities of the world of strangers is at the core of mall marketing, especially in its appeal to women and families (Pospěch, 2017). Consequently, municipal administrators find themselves in a difficult position, and they seek to even up their comparative disadvantage to privately run malls through incivility policing.…”
Section: Policing Incivility Regulating Urban Spacementioning
confidence: 99%
“…1841(Atkinson, -1842 The notion of a "street without its dangers" is a crucial reference when considered in the context of the rise of privately owned commercial spaces, such as shopping malls and privately owned developments, squares, and plazas (Pratt, 2017). Researchers have shown that the idea of an urban or quasi-urban street without the dangers and unpredictabilities of the world of strangers is at the core of mall marketing, especially in its appeal to women and families (Pospěch, 2017). Consequently, municipal administrators find themselves in a difficult position, and they seek to even up their comparative disadvantage to privately run malls through incivility policing.…”
Section: Policing Incivility Regulating Urban Spacementioning
confidence: 99%
“…In these analyses, shopping malls can accommodate multiple spatial narratives and performances, which the grand narrative of space colonised by spectacles and consumerist identity cannot account for (this is particularly true for shopping malls in cities beyond the West). To name a few examples, such narratives have examined carnivalesque and ludic plays in a Canadian mall (Shields, 1989); user- and community-based ethics and rhythms of inclusion in an Australian mall (Tyndall, 2008); shopping malls in Indonesia as heterotopic spaces posited ambiguously between Islam and phantasmagoria of urban modernity (Schmidt, 2012); and families’ pursuit of privacy, safety and comfort in the post-socialist Czech context (Pospěch, 2017).…”
Section: Public Space: Situated and Livedmentioning
confidence: 99%
“…Shopping centers in post-socialist countries have become one of the key signifiers of the modification of society's consumer behavior (cf. Pospěch 2017;Spilková 2003;Spilková and Radová 2011).…”
Section: Introductionmentioning
confidence: 99%